PERAN ORANG TUA TERHADAP TINGKAT KECEMASAN ANAK PADA SAAT PEMASANGAN INFUS DIINSTALASI GAWAT DARURAT (IGD) RSUD BANJARBARU - Zannah, Miftahul; Agustina, Rismia; Marlinda, Evy (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2015)
The infusion installation provided to a child at the time entering a hospital causes continuous trauma.It constitutes a procedure which brings about inconvenient feeling, fear and anxiety to the child. Therole of the parents during a child is treated in the hospital is a form of collaboration between thefamily and the medical profession and the presence of the parents provides a comportable feeling tothe child. This research is aimed at studying the relationship between the parents' role and the level ofchild's anxiety at the time of infusion installation at emergency care unit of Banjarbaru RegionalPublic Hospital. This research applies quantitative method with cross-sectional approach. Samplingis taken by using accidental sampling with the quantity of samples of 40 people. Data is obtained byusing observation sheets to the parents and the anxiety of the children, the data is tabulated andanalyzed. Analysis is made by applying chi-square analysis where a result of the value sig 0.001 (p <0,05) is obtained. From this research it can be concluded that there is a relationship between theparent's role and the level of a child's anxiety ath the time infusion installation.